Gender Inequality in West African Social Institutions - Bouchama, Nejma (West African Papers, 2018)
Discriminatory social institutions - formal and informal laws, social norms and practices - restrict women's rights and empowerment opportunities across 17 West African countries. New laws and measures to protect and promote women's economic, political and human rights have been accompanied by impressive reductions in gender gaps. However, discriminatory social institutions still constitute significant impediments to women's access to land assets and restrict women's physical integrity and decision-making power in both private and public spheres. This holds back women's education and economic empowerment, thereby decreasing countries' potential growth. The data and analysis based on the OECD Development Centre's Social Institutions and Gender Index (SIGI) aims to provide policy makers with the necessary tools and evidence to design more effective gender-responsive policies. Putting social institutions at the core of policy responses may open new and sustainable vistas to promote gender equality in national and regional development agendas